Challenges Faced by Teachers in Implementing the Merdeka Curriculum for Catholic Religious Education - Erikson Simbolon; Paulinus Tibo; Paulus Halek Bere (AL-ISHLAH: Jurnal Pendidikan, 2025)
The Merdeka curriculum was introduced to enhance the quality of Indonesian education and bridge the gap with other countries. Student learning achievement, assessed through standardized evaluations, serves as a key measure of this improvement. This study aims to identify the difficulties faced by teachers in adapting their teaching methods, the challenges in developing instructional modules, and the issues encountered in assessing Catholic religious education. This qualitative study employed observations, interviews, and document analysis to collect data from Catholic Religious Education teachers. Data were analyzed using data reduction, data presentation, and conclusion drawing. Findings indicate that teachers have implemented the Merdeka curriculum. However, they face significant challenges in transitioning from traditional teaching methods, designing effective teaching modules, and conducting assessments in accordance with the new system. These difficulties highlight the need for additional support and training. The study reveals that inadequate dissemination and technical guidance hinder effective curriculum implementation. Teachers require structured training and resources to successfully integrate the Merdeka curriculum into their teaching practices. While the Merdeka curriculum has been adopted, challenges remain in its execution. To ensure effective implementation, comprehensive training and equitable distribution of curriculum resources are necessary. Further research is recommended to explore long-term solutions for improving teacher adaptation.